2014
DOI: 10.1007/s40069-014-0073-4
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Use of MSWI Bottom Ash in Concrete

Abstract: An experimental investigation was carried out to evaluate the mechanical properties of concrete mixtures in which coarse aggregate was partially (30, 50 or 70 %) replaced with pre-washed municipal solid waste incineration (MSWI) bottom ash. Results indicated that bottom ash reduced the compressive strength, elastic modulus, and levels of heavy metals in leachate when used as a replacement for gravel, and that the maximum amount of MSWI bottom ash in concrete should not exceed 50 %. To analyze the effect mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(24 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…The cause of this effect was assigned to the high content of zinc and lead that could slow down concrete setting time forming a protective layer on cement grains (Quenee et al 2000). Furthermore, some studies have observed that initial and final setting time increased with the amount of cement replaced with BA (Zhang and Zhao 2014). To prevent the formation of spots or rust near concrete surface or expansion and road destruction, many authors suggested the application of a pre-treatment on BA as metal removal (Shih et al 2003;Pecqueur et al 2001) or thermal treatment ) in order to reduce the content of metals and enhance their mechanical properties.…”
Section: Concrete and Cementmentioning
confidence: 99%
“…The cause of this effect was assigned to the high content of zinc and lead that could slow down concrete setting time forming a protective layer on cement grains (Quenee et al 2000). Furthermore, some studies have observed that initial and final setting time increased with the amount of cement replaced with BA (Zhang and Zhao 2014). To prevent the formation of spots or rust near concrete surface or expansion and road destruction, many authors suggested the application of a pre-treatment on BA as metal removal (Shih et al 2003;Pecqueur et al 2001) or thermal treatment ) in order to reduce the content of metals and enhance their mechanical properties.…”
Section: Concrete and Cementmentioning
confidence: 99%
“…sugar cane bagasse [30], rice husk [31,32], barley husk [32]), thermally activated waste from rock extraction activity [33] or bottom ashes coming from municipal solid waste incineration [34].…”
Section: Cement Industrymentioning
confidence: 99%
“…Pastaraisiais metais pasaulinėje mokslinėje periodinėje spaudoje paskelbta nemažai publikacijų, susijusių su pelenų naudojimu betono mišiniams gaminti. Galima paminėti Van der Wegen et al (2013), Aggarwal, Sliddique (2014), Zhang, Zhao (2014), Kuo et al (2013), Lam et al (2010), Bertolinia et al (2004) darbus. Išskirtini Zhang, Zhao (2014), Collepardi et al (2015) darbai, kuriuose papildomai aukšta temperatūra paveikti dugno pelenai panaudoti inovatyvaus lengvojo ir savaime sutankėjančio betono mišinių gamybai.…”
Section: šLakų Naudojimo Statybos Pramonės Sektoriuje Pasaulinė Patirtisunclassified